Unique epitope-antibody interactions in the intrinsically disordered proteoglycan-like domain of human carbonic anhydrase IX defined by high-resolution NMR combined with yeast surface display - Feng Ni; Cunle Wu; Ping Xu; Ping Wang; Yves Fortin; Melanie Arbour; Luke Masson; Denis L'Abbé; Andrea Acel; Mylene Gosselin; Anne E.G. Lenferink (Taylor & Francis Group, 2023)
ABSTRACTCarbonic anhydrase (CA)-IX is an extracellular enzyme that is essential in the adaptation of tumor cells to their increasingly more hypoxic and acidic microenvironment. Within the family of carbonic anhydrases, CA-IX is unique in that it is the only CA with an N-terminal intrinsically disordered region (IDR) containing a proteoglycan (PG)-like domain. This PG-like IDR has been described to be instrumental in CA-IX's enzyme activity, as well as tumor cell motility and invasion. We have characterized the antibody-epitope interactions of two novel and unique antibodies (11H9 and 12H8) that are specific for the human CA-IX's IDR. Binding interactions of these antibodies to the intact IDR were studied by surface plasmon resonance and high-resolution nuclear magnetic resonance (NMR) spectroscopy, while the specific epitopes were determined by both NMR and yeast surface display (YSD). Our data show that 12H8 binds to the N-terminus of CA-IX, while 11H9 has a high affinity for an epitope located in the central region of the IDR containing three GEEDLP repeats in a manner that is different from the previously described M75 antibody. Titration NMR spectroscopy using CA-IX's entire IDR in addition identified a secondary epitope of 11H9 at the beginning of the PG-like domain that remains exposed and available for further binding events after the engagement at its primary epitope at the center of the PG-like domain. Transverse relaxation optimized NMR spectroscopy of 11H9-F(Ab) in complex with the CA-IX IDR outlines structural rigidification of a linear epitope, while the rest of the IDR remains largely unstructured upon complex formation. This study illustrates how high-resolution NMR and YSD are used as complementary tools for a comprehensive characterization of antibody-epitope interactions involving intrinsically unstructured antigen domains with highly repetitive sequences.